Pola Komunikasi Guru- Siswa di Sekolah Slanker (MA NU 03 Brebes) Melalui Sistem Perbaikan Karakter - Endang Listiani; Ike Desi Florina; Sarwo Edy, M.I.Kom (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
The purpose of this study was: to determine the communication patterns used by educators to students in order to improve character in the Brebes SLANKER School. This research uses social penetration theory. The data analysis technique used is descriptive qualitative, where the authors collect existing data, compile systematically, then describe the results of the study based on the images or data obtained during the study. The results of this study indicate that the pattern of communication between teachers and students in SLANKER schools (Madrasah Aliyah NU 03 Brebes) through the education system is able to improve student character. With the use of two-way and multi-directional communication patterns through the education system with the arts and storytelling, it can improve student character in the form of manners.